Efferocytosis-induced metabolic shift in bone macrophages drives lactate production and modulates inflammation and osteoclastogenesis - Kannan, Rahasudha; Carruthers, Nicholas J.; Koh, Amy J.; Kleer, Gabriel G.; Nakamura, Kotoba; Parker, Stephen C. J.; McCauley, Laurie K.; Roca, Hernan (Frontiers in Immunology, 2025)
During the critical process of homeostatic efferocytosis, macrophages clear apoptotic cells and subsequently transition to reparative functions that promote the resolution of inflammation and support tissue repair. Their inherent plasticity enables rapid changes in macrophage activity suited to specific microenvironments. However, the heterogeneity in their cell states also presents challenges in characterizing subsets of macrophages and analyzing their specific contributions post-efferocytosis. In this study, single-cell RNA sequencing data from bone-marrow derived macrophages engulfing apoptotic osteoblasts (OB) was used to characterize macrophage subpopulations enriched during efferocytosis. Clustering analysis revealed two subpopulations (c3 and c9) that were unique to efferocytic macrophages. These distinct subpopulations displayed a transcriptional profile characterized by enhanced glycolytic energy metabolism, along with an anti-inflammatory gene signature. Notably, HIF-1 signaling, glycolysis/gluconeogenesis, and carbon metabolism were among the top five most significantly enriched pathways in c3 and c9 macrophages. qRT-PCR analysis revealed that macrophages engulfing apoptotic OBs exhibited increased expression of key glycolytic enzymes and solute carriers, including Slc2a1, Pdk1, Ldha, and Slc16a3. Metabolomics analysis revealed a significant increase in intracellular lactate, phosphoenolpyruvic acid, glycerol-3-phosphate, 2-/3-glycerophosphate, and fructose-6-phosphate, indicative of enhanced glycolysis. In addition, efferocytic macrophages showed increased extracellular lactate production compared to control macrophages, as confirmed by lactate ELISA. The effects of lactate (0-20mM) on osteoblast mineralization, osteoclast differentiation and function, and macrophage-derived inflammatory factors were evaluated through various in vitro experiments. While no effect was seen in osteoblast mineralization, high lactate concentrations significantly reduced the number of multinucleated osteoclasts and their resorptive activity. Interestingly, extracellular lactate also significantly upregulated M2-like macrophage markers (Arg1, Il1rn, Klf4). These results support the concept that macrophage efferocytosis of apoptotic osteoblasts alters macrophage energy metabolism, which in turn plays a distinct and pivotal role in modulating the bone microenvironment.